Efek Magneto Optis pada Lapisan Tipis (ZnO) - Adi, Muhamad; Firdausi, K. Sofjan; Setia Budi, Wahyu (BERKALA FISIKA, 2007)
The magneto optics phenomenon on a thin film has been observed using Michelson Interferometer. The transparent materials used in the experiment is a cover glass (thickness of 1 mm) coated by the thin film ZnO (Zincite) in 54 mm of thickness. An external magnetic field which is applied to the transparent materials is in the order of 184,95 mTÂ  obtained by a coil inserted by a soft magnet and given by the alternating current. To obtain the change of refractive index, an Michelson Interferometer has been used using He-Ne laser with = 632,8 nm and output power of 1 mW. The change of phase or refractive index of ZnO is very clearly shown by the increasing of number of fringes as the magnetic fields increases. The order of the linear coefficient magneto optics is 10-10 m/V indicates that it is very reactive to a external applied field. Keywords: Michelson Interferometer, Non-linear Optics, Refraction Index and Linear Magneto-optic Coefficients